Impact of appropriate use criteria for transesophageal echocardiograms on clinically meaningful care. Issue 1 (18th November 2018) - Gupta, Tripti; Jahangir, Eiman; Gilliland, Yvonne; Lavie, Carl J.; Shah, Sangeeta
Abstract : Introduction: The aim of this study was to evaluate appropriateness of transesophageal echocardiography (TEE) studies based on 2011 Appropriate Use Criteria (AUC) for Echocardiography and its impact on patient management. Methods and Results: In a retrospective analysis of 100 inpatient TEEs, 85% of the TEEs ordered were determined to be appropriate, 9% were inappropriate, and 6% were uncertain. Inter‐observer differences in the determination of AUC were seen in 24% of the studies, requiring a senior‐level cardiologist to make the final determination of AUC score. The variance in interpretation by experts is concerning for how that might translate into differences in clinical practice. Of all TEEs, only 63% led to an active change in care, including changes in medications or procedures, while 37% did not. We found a statistically significant difference between cardiologists' and non‐cardiologists' orders for TEE having an impact on patient's clinical care (41% vs 22%, respectively, P  <   0.05) (Table2 ). While not statistically significant, a trend toward clinical change was observed in the appropriate vs inappropriate TEEs (70% vs 44%, respectively, P  =   0.06). Conclusion: Ideally, the role of a diagnostic cardiovascular imaging test, such as a TEE, is to influence clinical care, if it is ordered appropriately on the right patient. While the AUC guides clinicians on the appropriate use of cardiovascular imaging, it is broadly written and offers room for interpretation to encompass variety of clinical scenarios. Clinical care paths that utilize AUC and standardize use of multidisciplinary institutional resources offer opportunity for optimal clinical impact and patient care.